O bônus demográfico relativo e absoluto no acesso à escola - Sergei Suarez Dillon Soares (Instituto de Pesquisa Econômica Aplicada (IPEA), 2008)
– This text proposes a methodology for classifying the demographic bonus in education into relative and absolute components. According to this definition, a relative demographic bonus means that school age-population is increasing more slowly than total population, making more resources available, relative to population size, for education. An absolute bonus means that school age population is actually shrinking, making more resources per child available in absolute terms. The definition is operationalized through a decomposition of changes in net enrollment rates. This methodology is then applied to eleven Latin-American countries (Bolivia, Brazil, Costa Rica, Uruguay, Venezuela, Argentina, Ecuador, Guatemala, Honduras, Mexico, and Panama). The results indicate that the only country enjoying an absolute demographic bonus in education in Brazil, although Mexico and Panama are reaping large relative bonuses. Another group of countries is composed by Uruguay, Argentina, Cost Rica, and Ecuador, in which changes in net enrollment rates have been small and population stable, meaning there is nothing to explain or decompose. Finally, a group of principally small countries composed of Bolivia, Venezuela, Honduras, and Guatemala still enjoy only either a small demographic bonus or even no bonus at all. Surprisingly, it was in these countries that the greatest increases in net enrollment rates are observed, suggesting that demographics, while important, are not the only determinant of educational results.
Keywords: J11; 330